An integrated enrichment system to facilitate isolation and molecular characterization of single cancer cells from whole blood. Issue 12 (14th December 2018) - Yu, Liping; Sa, Silin; Wang, Ling; Dulmage, Keely; Bhagwat, Neha; Yee, Stephanie S.; Sen, Moen; Pletcher, Charles H.; Moore, Jonni S.; Saksena, Suraj; Dixon, Eric P.; Carpenter, Erica L.
Abstract: Circulating tumor cells (CTCs) carry valuable biological information. While enumeration of CTCs in peripheral blood is an FDA‐approved prognostic indicator of survival in metastatic prostate and other cancers, analysis of CTC phenotypic and genomic markers is needed to identify cancer origin and elucidate pathways that can guide therapeutic selection for personalized medicine. Given the emergence of single‐cell mRNA sequencing technologies, a method is needed to isolate CTCs with high sensitivity and specificity as well as compatibility with downstream genomic analysis. Flow cytometry is a powerful tool to analyze and sort single cells, but pre‐enrichment is required prior to flow sorting for efficient isolation of CTCs due to the extreme low frequency of CTCs in blood (one in billions of blood cells). While current enrichment technologies often require many steps and result in poor recovery, we demonstrate a magnetic separator and acoustic microfluidic focusing chip integrated system that enriches rare cells in‐line with FACS™ (fluorescent activated cell sorting) and single‐cell sequencing. This system analyzes, isolates, and index sorts single cells directly into 96‐well plates containing reagents for Molecular Indexing (MI) and transcriptional profiling of single cells. With an optimized workflow using the integrated enrichment‐FACS system, we performed a proof‐of‐concept experiment with spiked prostate cancer cells in peripheral blood and achieved: (i) a rapid one‐step process to isolate rare cancer cells from lysed whole blood; (ii) an average of 92% post‐enrichment cancer cell recovery ( R 2 = 0.9998) as compared with 55% recovery for a traditional benchtop workflow; and (iii) detection of differentially expressed genes at a single cell level that are consistent with reported cell‐type dependent expression signatures for prostate cancer cells. These model system results lay the groundwork for applying our approach to human blood samples from prostate and other cancer patients, and support the enrichment‐FACS system as a flexible solution for isolation and characterization of CTCs for cancer diagnosis. © 2018 International Society for Advancement of Cytometry Abstract :